The Mental Vulnerability of Affordable Housing Residents Based on Structural Equation Model: A Case Study of Fanghe Garden in Guangzhou - Zhang, Yuanyuan; Li, Liling; Tang, Bo; Lin, Lin (Frontiers in Psychology, 2022)
By constructing a “measure-representation-mechanism” research paradigm of mental vulnerability, this manuscript explores the mental vulnerability measures, spatial representations, and influencing factors of affordable housing residents in Fanghe Garden in Guangzhou by combining the mental vulnerability questionnaire (MVQ) and the structural equation model (SEM). First, the residents of Fanghe Garden had a higher mental vulnerability, difficulties in interpersonal interaction, and lower well-being. Second, the behavioral spatial representations of residents’ mental vulnerability were significantly differentiated. Low-rent housing residents were less active and preferred hidden and small places, while economically affordable housing residents were more active, and they concentrated their activity space in the cultural gallery and central square. Residents were highly willing to interact with neighbors within the community, but mainly with similar people. Third, housing condition, community construction, physical condition, neighborhood communication, and housing experience had a significant negative effect on the mental vulnerability of affordable housing residents.